PENGARUH PENDAPATAN PERKAPITA, INVESTASI DAN INFLASI TERHADAP KEMISKINAN DI PROVINSI SUMATERA UTARA - Febriaty, Hastina; Nurwani, Nurwani (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2017)
In this research was discusses the influence of per capita income, investment and inflation on poverty in North Sumatra Province. The purpose of this research is to know the influence of per capita income, investment and inflation on poverty in North Sumatera province partially and simultaneously, and the variable that has dominant influence to poverty in North Sumatera Province. Sources of data used are secondary data taken from the Central Bureau of Statistics and Bank Indonesia from 2001 to 2015.Teknik analysis used in this study is multiple linear regression analysis using e-views program 8.1 and perform testing of classical assumptions and using hypothesis testing simultaneously (F) and partial (t).The results showed that partially per capita income had negative and significant effect to poverty in North Sumatera Province. Investment had negative and insignificant effect on poverty in North Sumatera Province while Inflation had positive and insignificant effect on poverty in North Sumatera Province. Simultaneously per capita income, investment and inflation affect poverty in North Sumatera ProvinceKeywords: Per capita Income, Investment, Inflation and Poverty